The SpongeBob movie : search for SquarePants [videorecording (DVD)] - Ceccarelli, Marc; Kaz, 1959- (Paramount, 2026)
SpongeBob and his Bikini Bottom friends set sail in their biggest, all-new, can't miss cinematic event ever... The SpongeBob Movie: Search for SquarePants. Desperate to be a big guy, SpongeBob sets out to prove his bravery to Mr. Krabs by following The Flying Dutchman, a mysterious swashbuckling ghost pirate, on a seafaring comedy adventure that takes him to the deepest depths of the deep sea, where no Sponge has gone before.